Novel Approaches to Control Adipocyte Differentiation Through Modulation of ER Stress and Growth Differentiation Factor 15 - 김행준 (The Graduate School, Ajou University, 2024)
과도한 지방세포 분화 및 축적은 비만, 당뇨병, 고지혈증 등의 대사 장애 발병에 기여합니다. 지방분화는 여러 호르몬과 다양한 전사인자들의 상호작용을 통하여 매우 복잡하게 이루어진다. 이중 지방세포의 분화조절은 퍼옥시좀 증식자 활성화 수용체 감마(PPARγ), CCAAT/인핸서 결합 단백질 (C/EBPs) 전사인자가 지방세포의 분화에 있어서 중추적인 역할을 담당하고 있다._x000D_ 첫번째 연구에서 우리는 비열플라즈마 처리액(NTS)이 지방생성을 억제하는 효과가 있는지 조사하고 그 메커니즘을 규명하였다. 우리의 결과는 NTS가 Oil Red O염색 및 트리글리세리드 축적 확인을 통하여 지방 전구세포의 지방세포로의 분화를 유의미하게 억제한다는 것을 보여주었다. 또한 NTS처리는 주요 지방생성전사인자 및 지방세포 특이적 유전자의 mRNA 및 단백질 발현 수준을 억제했다. 지방분화를 억제하는 메커니즘으로 우리는 지방 분화 과정에서 증가하는 ER 스트레스 관련 마커들이 NTS에 의해 하향 조절하는 것을 확인하였다. In vitro 연구와 일관되게, 식이 유발 비만 마우스 모델을 사용한 in vivo연구에서도 NTS치료가 음식 섭취량의 변화 없이 체중과 지방을 감소시키는 것으로 나타났다. 이러한 발견은 NTS가 지방 생성분화를 억제하고 지방 생성에 대한 NTS의 억제효과에 대한 메커니즘을 설명한다. 종합적으로 우리의 결과는 NTS가 이미 알려져 있는 어려 생체의학 분야뿐만 아니라 비만 및 비만 관련 질병을 치료하는데 유용할 수 있음을 시사한다. _x000D_ 두번째 연구에서는 성장 분화 인자 15(GDF15)와 지방세포 분화의 관계에 대해서 확인하였다GDF15는 에너지 항상성과 관련된 스트레스 반응 사이토카인으로 간주되며, 이는 수용체인 GDNF 계열 수용체 알파 유사(GFRAL) 메커니즘을 통해 에너지 소비를 증가시키고 음식 섭취량과 체중을 억제함으로써 이루어진다. 그 효과에도 불구하고 GDF15 혈청 수준은 비만 쥐와 인간에게서 증가한다. 인간 지방생성 초기단계 동안 GDF15 단백질 전환 메커니즘과 GDF15 과발현에 의해 매개되는 하류 신호전달 경로는 평가되지 않았다. 여기에서 우리는 부고환 백색 지방 조직(eWAT)의 GDF15 단백질과 혈청 GDF15 수준이 정상적인 식단에 비해 단기 HFD 공급을 받는 쥐에서 상당한 감소를 보인다는 것을 발견하였다. 유사하게, 지방생성 분화 배지를 사용하여 인간 지방 유래 줄기세포(ADSCs)에서 지방세포로의 분화를 유도하는 동안, GDF15 단백질은 초기 지방생성에서 감소하였다. 기계적으로 GDF15는 초기 지방생성 과정에서 자가포식 리소좀 경로(ALP)를 통해 주로 분해된다. 지방전구세포에서의 GDF15 과발현은 지방생성 분화 배지에서 CCAAT 인핸서 결합 단백질 알파(CEBPα)의 유도를 차단함으로써 지방생성을 억제한다. 다음으로 우리는 HOP2가 지방생성 동안 감소하는 것으로 알려져 있지만, 상승된 GDF15 조건에서 증가된다는 것을 발견했다. 더욱이, GDF15가 과발현되었을 때 C/EBPα의 감소가 관찰되었지만, HOP2가 녹아웃 되었을 때 이러한 감소는 발생하지 않았다. 이러한 발견은 지방세포 분화를 억제하는 데 있어 GDF15의 역할을 밝히고 이러한 억제의 기본 메커니즘에 대한 통찰력을 제공한다._x000D_ 결론적으로, 우리의 결과는 GDF15가 이전에 보고된 바와 같이 체중 감량제 역할을 할 뿐만 아니라 지방세포 분화 억제를 하여 체중 증가 조절제로서의 잠재력을 제공할 수 있음을 시사합니다.|Excessive adipocyte differentiation and accumulation are correlated with the onset of metabolic disorders such as obesity, diabetes, and hyperlipidemia. Adipocyte differentiation is a highly intricate process mediated by the interaction of various hormones and transcription factors. Among them, the regulation of adipocyte differentiation is primarily governed by peroxisome proliferator-activated receptor gamma (PPARγ) and CCAAT/enhancer-binding proteins (C/EBPs), which play a central role in regulating adipocyte differentiation. In the first study, we investigated the inhibitory effect of non-thermal plasma- treated solution (NTS) on adipogenesis and elucidated its mechanism. Our findings indicate a notable suppression of pre-adipocyte differentiation into adipocytes by NTS, as evidenced by Oil Red O staining and validated through the assessment of triglyceride accumulation. Furthermore, NTS treatment suppressed the mRNA and protein expression levels of major adipogenic transcription factors and adipocyte- specific genes. The mechanism underlying adipogenesis inhibition revealed that NTS downregulates ER stress-related markers, which increase during the adipogenic process. Consistently, in vivo studies using a diet-induced obesity mouse model demonstrated that NTS treatment reduced body weight and fat content without dietary modification. These findings demonstrate that NTS inhibits adipogenic differentiation and explain the mechanism for the inhibitory effect of NTS on adipogenesis. Overall, our results suggest that NTS could be beneficial not only in established biomedical fields but also in treating obesity and related conditions. The study implies the potential usefulness of NTS in addressing obesity-related disorders. In the second study, we investigated the relationship between growth differentiation factor 15 (GDF15) and adipocyte differentiation. GDF15 is considered a stress- responsive cytokine associated with energy homeostasis, achieved through the GDNF family receptor alpha-like (GFRAL) mechanism, increasing energy expenditure and suppressing food intake and body weight. Despite its effectiveness, GDF15 serum levels are increased in obese mice and humans. However, the protein conversion mechanism of GDF15 and downstream signaling pathways mediated by GDF15 overexpression during early human adipogenesis remain unevaluated. Here, we discovered a substantial decrease in GDF15 protein in epididymal white adipose tissue (eWAT) and serum GDF15 levels in mice subjected to short-term HFD supply compared to a normal diet. Similarly, during the induction of adipocyte differentiation from human adipose-derived stem cells (ADSCs) using adipogenic differentiation media, GDF15 protein decreased during early adipogenesis. Mechanistically, GDF15 is predominantly degraded through the autophagic lysosomal pathway (ALP) during early adipogenesis. GDF15 overexpression in pre-adipocytes inhibits adipogenesis by blocking the induction of CCAAT enhancer binding protein alpha (CEBPα) in adipogenic differentiation media. Additionally, we found that while HOP2 is known to decrease during adipogenesis, it increases under elevated GDF15 conditions. Moreover, although a decrease in C/EBPα was observed when GDF15 was overexpressed, this decrease did not occur when HOP2 was knocked down. Our findings reveal the role of GDF15 in suppressing adipocyte differentiation and provide insight into the mechanisms underlying this suppression. In conclusion, our results suggest that GDF15 not only acts as a weight loss agent but may also regulate adipocyte differentiation, offering its potential as a regulator of weight gain.
학위논문(박사)--분자과학기술학과,2024. 2
Keywords: C/EBPα; ER stress; GDF15; HOP2; Plasma; adipogenesis